Hubungan Antara Status Gizi dan Pola Makan dengan Kejadian Anemia Pada Remaja Putri - Anis Muhayati; Diah Ratnawati (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2019)
Anemia is one of the nutritional problems in adolescent girls. Anemia is a condition in when blood hemoglobin levels are less than normal (<12gr / dl) in women characterized by clinical symptoms: lethargy, weakness, dizziness, blurred eyes, and pale faces. This study aims to determine the relationship of nutritional status and diet with phenomenon of anemia in adolescent girls in SMA Negeri 97 Jakarta. The design of this research is quantitative with cross sectional approach. The subjects of this study are 188 adolescent girls selected stratified random sampling. Bivariate analysis using chi-square test with 95% confidence level. The result of pearson chi-square test showed that there was a significant correlation between nutritional status and phenomenon of anemia in adolescent girls with p value = 0.008 (<0.05). Analysis of diet with phenomenon of anemia in adolescent girls using continuity correction test with p value = 0.004 (<0.05) which means there is relationship between diet with phenomenon of anemia with value of OR = 0407. Adolescent girls in SMA Negeri 97 Jakarta should pay more attention to diet and nutritional status so as to prevent the phenomenon of anemia in adolescents that interfere with the learning and activity of adolescents.